2012
DOI: 10.1039/c2np00090c
|View full text |Cite
|
Sign up to set email alerts
|

Marine natural products

Abstract: Covering: 2010. Previous review: Nat. Prod. Rep., 2011, 28, 196. This review covers the literature published in 2010 for marine natural products, with 895 citations (590 for the period January to December 2010) referring to compounds isolated from marine microorganisms and phytoplankton, green, brown and red algae, sponges, cnidarians, bryozoans, molluscs, tunicates, echinoderms, mangroves and other intertidal plants and microorganisms. The emphasis is on new compounds (1003 for 2010), together with the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
304
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(309 citation statements)
references
References 870 publications
(733 reference statements)
1
304
0
4
Order By: Relevance
“…Recently, Blunt and co-workers indicated that the structures for the highly brominated derivatives 695−697 should be re-examined because of inconsistencies in the published NMR data for these compounds. 401 …”
Section: Other Halogenated Organic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Blunt and co-workers indicated that the structures for the highly brominated derivatives 695−697 should be re-examined because of inconsistencies in the published NMR data for these compounds. 401 …”
Section: Other Halogenated Organic Moleculesmentioning
confidence: 99%
“…Compounds of this class are generally brominated, with three of them chlorinated (407−409) 258 and four bromochlorinated (410, 411, 258 415, 72 and 416). 264 The first halogenated THF ACG to be reported was laureepoxide (401), which was isolated from L. nipponica collected from Hokkaido, Japan. 260 This compound is also the first example of a brominated ACG derivative containing both oxolane and oxirane rings.…”
Section: Halogenated Nonterpenoid C 15 -Acetogenins (Acgs)mentioning
confidence: 99%
“…1,2) When marine-derived microorganisms are cultured under saline conditions, they rarely produce interesting biological halogenated metabolites (e.g., salinosporamide A, 3) a highly potent inhibitor of the 20S proteasome, and its halogenated derivatives 4) ; cytotoxic halogenated polyenyl pyrroles, isorumbrin and bromoisorumbrin 5) ; the nematicidal and antimicrobial lachnumon and mycorrhizin A derivatives 6) ; bromomyrothenone B 7) ; and the antibacterial chlorohydroaspyrones A and B 8) ). Encouraged by the detection of bioactive halogenated marine analogs, and in an effort to gain access to a wider cross-section of halogenated secondary metabolites, we manipulated fermentation of the marine-derived fungi Phoma herbarum, Penicilliun chrysogenum, Fusarium tricinctum, and Dothideomycete sp.…”
mentioning
confidence: 99%
“…The triturated fractions were subjected to HPLC-DAD-ESI-MS analysis. Further confirmation about the structure was achieved with 13 C NMR data comparison to that in literature ( Carduusynes can undergo solvolysis in EtOH to generate the respective ethyl esters as evident from the isolation and characterisation of carduusynes A-E. 173 In the current study, we isolated a new analogue, carduusyne F ethyl ester, further indicating the existence of its acetylenic acid natural product carduusyne F (2.04). conditions at 30 µM but did not show any activity at lower concentrations.…”
Section: Secondary Screening and Prioritisationmentioning
confidence: 75%
“…NMR (DMSO-d 6 ) data for 3.02 revealed similarities with that of 3.01, with the key differences apparent in the 13 to C-7a'') with a sp 3 methine (C-6'''), a primary methyl (C-7'''), and a C-2'''-imidazole moiety in required NH-1 and the H 3 -7 to be on the same plane, and established a relative stereochemistry in common with dragmacidin E (3.02). Furthermore, a similar cotton effect in the CD spectra of 3.02 and 3.03 (Figure 3.11) strongly supported the proposed stereochemistry.…”
Section: Dragmacidin E (302)mentioning
confidence: 93%